Jezikovni prenos pri učenju sorodnih jezikov - Balažic Bulc, Tatjana (Jezik in slovstvo, 2004)
Communicative competence developed in the firts language (L1), is the basis for developing communicative competence when later learning a foreign/second language (FL/ L2). Quite often in this process a linguistic transfer occurs, both positive and negative. On the basis of a digitalised corpus of language acquisition consisting of written exams in Slovene, an analysis of negative linguistic transfer between two most closely related languages, Serbo-Croatian (L1) and Slovene (FL/L2) was made. The article shows part of the research correlated to the systemisation and types of mistakes arising from such a transfer. It is evident from the anakysis of mistakes which areas need additional attention while learning Slovene as FL/F2 to the speakers of Serbo-Croatian.
Keywords: Slovene; slovenščina; slovenščina kot drugi ali tuji jezik; srbohrvaščina; sociolinguistics; sociolingvistika; jezikovni pouk; jezikovni prenos